2016
DOI: 10.11604/pamj.2016.23.125.8936
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and uptake of health insurance for maternal care in rural Kenya: a cross sectional study

Abstract: IntroductionIn Kenya, maternal and child health accounts for a large proportion of the expenditures made towards healthcare. It is estimated that one in every five Kenyans has some form of health insurance. Availability of health insurance may protect families from catastrophic spending on health. The study intended to determine the factors affecting the uptake of health insurance among pregnant women in a rural Kenyan district.MethodsThis was cross-sectional study that sampled 139 pregnant women attending the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
24
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 13 publications
8
24
2
Order By: Relevance
“…In particular, poor financial protection in low resource settings is attributable to inadequate funding, fragmentation of healthcare resources, and inadequate health insurance coverage [16]. Similar to the findings of our study, previous studies have also shown that direct OOP costs place a huge burden of bearing the costs of illness to the sick person and their households, and is therefore, a major contributor to inequities [37][38][39][40][41]. Providing financial risk protection to reduce OOP health expenditure as envisaged in the Sustainable Development Goals and UHC agendas are critical to improving access to primary healthcare in resource-poor urban settings.…”
Section: Discussionsupporting
confidence: 82%
“…In particular, poor financial protection in low resource settings is attributable to inadequate funding, fragmentation of healthcare resources, and inadequate health insurance coverage [16]. Similar to the findings of our study, previous studies have also shown that direct OOP costs place a huge burden of bearing the costs of illness to the sick person and their households, and is therefore, a major contributor to inequities [37][38][39][40][41]. Providing financial risk protection to reduce OOP health expenditure as envisaged in the Sustainable Development Goals and UHC agendas are critical to improving access to primary healthcare in resource-poor urban settings.…”
Section: Discussionsupporting
confidence: 82%
“…In particular, poor financial protection in low resources settings is attributable to inadequate funding, fragmentation of healthcare resources and inadequate health insurance coverage (32). Similar to the findings of our study, previous studies have also shown that direct (out of pocket) OOP costs place a huge burden of bearing the costs of illness to the sick person and their households, and is, therefore, a major contributor to inequities (38)(39)(40)(41)(42). Providing financial risk protection to reduce OOP health expenditure as envisaged in the Sustainable Development Goals and UHC agendas is critical to improve access to primary healthcare in resource-poor urban settings.…”
Section: Discussionsupporting
confidence: 82%
“…In particular, poor nancial protection in low resources settings is attributable to inadequate funding, fragmentation of healthcare resources, and inadequate health insurance coverage [34]. Similar to the ndings of our study, previous studies have also shown that direct (out of pocket) OOP costs place a huge burden of bearing the costs of illness to the sick person and their households, and is, therefore, a major contributor to inequities [40][41][42][43][44]. Providing nancial risk protection to reduce OOP health expenditure as envisaged in the Sustainable Development Goals and UHC agendas are critical to improving access to primary healthcare in resource-poor urban settings.…”
Section: Discussionsupporting
confidence: 82%